STRUCTURAL ORGANIZATION MULTILEVEL SCHEMES WITH MEMORY GENERAL AUTOMATA STRATEGY (Transport systems and technologies, 2018)
The publication revealed the essence of the theory of building a multilevel memory circuits, as well as an example of simulated multi Grade 1 circuits. Comparison and analysis capabilities of the trigger and the gun BFSP with the general strategy of multilevel memory circuits. The methods of synthesis and BFSP BRSP on their character description that allows to formalize their design with the limitations of logic elements by the number of units and load capacity. The existing circuit components computers (new multilevel memory circuits), as well as new developments Marahovskoho L. in the field of synthesis and analysis and multi-tiered storage schemes.
Keywords: multi-level memory circuit, the new element base, the device strategy